Muscle Size and Strength Benefits of Functional Electrical Stimulation-Evoked Cycling Dosage in Spinal Cord Injury: A Narrative Review - Rosley, Nurhaida; Hamzaid, Nur Azah; Hasnan, Nazirah; Davis, Glen Macartney; Manaf, Haidzir (Penerbit Universiti Kebangsaan Malaysia, 2019)
Loss of sensory motor function is one of the main causes of physical and activity limitations among individual with spinal cord injury (SCI). SCI may lead to muscle paralysis, weakness and disused muscle atrophy. Evidences have shown electrical stimulation and strengthening exercise might improve lower limb muscle strength and size among individual with SCI. Functional electrical stimulation (FES) evoked cycling is one of the methods that can elicit leg muscle contractions in order to produce a cycling motion and promote the integrity of the involved muscles. Therefore, this review is to synthesize the scientific literature regarding the effects of multiple dosages of FES-evoked lower limb cycling on muscle properties. A systematic literature search from 1946 to 2016 was performed. From over 1,139 articles retrieved from the database, about 31 potentially relevant articles were retained for possible inclusion. However, only 10 articles out of 31 articles fulfilled the inclusion criteria. Although the available evidence is compelling, there is insufficient quantity and quality evidence to draw conclusions regarding the specific parameter of FES-CE that may optimally increase muscle strength, mass, and circumference. However, it can be safely concluded that an effective training session would spend for 45-60 min, 3 times a week for at least 4 weeks to see changes in muscle size and strength. © 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.